Feasibility of the Betangas Concoction Handbook for Treating Vertigo as a Learning Media for Nervous System Submaterials - Grasilla, Gisa; Panjaitan, Ruqiah Ganda Putri; Fajri, Hayatul; Ningsih, Kurnia (Bioscientist : Jurnal Ilmiah Biologi, 2024)
Biology is a subject about living things and their relationship with the nature environment. One thing that can be support the biology learning process is a media. A pocket book is a medium that is small, easy to carry and can be read at any time. This study aims to determine the feasibility of the betangas herb of pocket book media for treating vertigo. The pocketbook is tested for suitability by five validators. There are four aspects assessed namely, format, content, language and graphics. The research results show the value for the format aspect is 1, the content aspect is 1, the language aspect is 1, and the graphic aspect is 1. The results of the validation show a CVI value of 1. So it can be concluded that the betangas herb pocket book media for treating vertigo as a learning medium for nervous system sub-materials can be declared feasible.